Error Correction Codes For Redundant Parallel Filters - S, Veena; Reddy, M Seshananda; Reddy, T Nikhileswara; Sudarshan, V R; Kumar K, Vinay (IJRDO - Journal of Electrical And Electronics Engineering, 2016)
The objective of this paper is to propose a simple technique that exploits the presence of parallel filters to achieve fault tolerance. Fault tolerance means a system will continue to work properly even if the fault has occurred in the system. Now a day’s digital filter are used in the signal processing systems and in communication systems. In some situations the consistently perform of the system becomes difficult, hence the fault tolerant implementation is needed. Over the period many techniques has been evolved to achieve the fault tolerance. A new technique has been developed, in which the fault tolerance will enables more complex systems tha include many filters. in those complex system, most commonly the parallel filters are used. In brief ,the fault tolerance is used to protect the parallel filters from the Error Correction Codes (ECCs).The new technique allows more efficient protection when the number of parallel filters are more in the system. The technique is proposed using parallel finite impulse response filters showing the effectiveness in terms of protection and implementation cost